The global distribution and evolutionary history of the pT26‐2 archaeal plasmid family - Catherine Badel; Gaël Erauso; Annika L. Gomez; Ryan Catchpole; Mathieu Gonnet; Jacques Oberto; Patrick Forterre; Violette Da Cunha (Environmental Microbiology, 2019)
Summary Although plasmids play an important role in biological evolution, the number of plasmid families well‐characterized in terms of geographical distribution and evolution remains limited, especially in archaea. Here, we describe the first systematic study of an archaeal plasmid family, the pT26‐2 plasmid family. The in‐depth analysis of the distribution, biogeography and host–plasmid co‐evolution patterns of 26 integrated and 3 extrachromosomal plasmids of this plasmid family shows that they are widespread in Thermococcales and Methanococcales isolated from around the globe but are restricted to these two orders. All members of the family share seven core genes but employ different integration and replication strategies. Phylogenetic analysis of the core genes and CRISPR spacer distribution suggests that plasmids of the pT26‐2 family evolved with their hosts independently in Thermococcales and Methanococcales, despite these hosts exhibiting similar geographic distribution. Remarkably, core genes are conserved even in integrated plasmids that have lost replication genes and/or replication origins suggesting that they may be beneficial for their hosts. We hypothesize that the core proteins encode for a novel type of DNA/protein transfer mechanism, explaining the widespread oceanic distribution of the pT26‐2 plasmid family.